1985
DOI: 10.2337/diab.34.12.1222
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Axonal Transport in Rat Ileal Mesenteric Nerves: Characterization Using Intravenously Administered 125I-Nerve Growth Factor and Effect of Chemical Sympathectomy

Abstract: We have previously demonstrated the reproducible occurrence of dystrophic axonopathy and a defect in the retrograde axonal transport of 125I-nerve growth factor (125I-NGF) involving postganglionic sympathetic axons in the alimentary tract of rats with chronic streptozocin (STZ)-induced diabetes. To avoid complexities inherent in monitoring the accumulation of 125I-NGF in the superior mesenteric ganglion as a measure of retrograde transport in the peripheral axons of the extensive alimentary territory, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Support to this view comes from the fact that diabetic complications are a rarity when DM is secondary to other diseases like chronic pancreatitis (20). Experimentally, it has been shown that alloxan and streptozotocin-induced DM is associated with neuropathy, and with impairment of NGF transport in nerve fibers (21)(22)(23); interestingly, an ultrastructural study described vacuolization and rupture of granules in the granular tubulary cells of the submaxillary gland that produce NGF in streptozotocin-treated rats (24).…”
Section: Discussionmentioning
confidence: 99%
“…Support to this view comes from the fact that diabetic complications are a rarity when DM is secondary to other diseases like chronic pancreatitis (20). Experimentally, it has been shown that alloxan and streptozotocin-induced DM is associated with neuropathy, and with impairment of NGF transport in nerve fibers (21)(22)(23); interestingly, an ultrastructural study described vacuolization and rupture of granules in the granular tubulary cells of the submaxillary gland that produce NGF in streptozotocin-treated rats (24).…”
Section: Discussionmentioning
confidence: 99%
“…(14) 6.24 * 2.59 (14) Operated 9.47 f 0.54 (7) 4.28 +-1.35 (7) 9.94 * 0.69 (14) 3.45 2 2.23t (14) Normal 12.69 2 1.04 (7) 1.82 2 0.71 (7) 13.24 f 0.83 (14) 1.70 2 0.83 (14) Operated 12.94 2 1.12 (7) 1.42 f 0.69 (7) 13.442 0.83 (14) 1.13 * 0.48t (14) Normal 18.07 ? 1.43 (7) 3 04 f 0.90 (7) 18.77 * 1.00 (14) 3.24 f 1.13 (14) 2.30 f 0.96 (7) 19.05 2 1.06 (14) 1.94 f 0.71t (14) From these studies, factors that may affect the outcome are related to age, type and level of injury, length of ischemia, time interval from injury to repair, skeletal shortening, etc6 In toe-to-digit transplantation, emphasis has been placed on the recovery of two-point discrimination for correlation with hand f u n~t i o n .~"~"~*~~ However, functional evaluation of the transplanted toes in previous reports was usually inadequate or in need of more detailed data. Therefore, this report is the first to combine clinical sensory testing with electrophysiological study to evaluate recovery of function in toe-to-digit transplantation in a relatively large number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…NGF is retrogradely transported in sensory and sympathetic neurons in adult rats (Hendry et a l . 1974;Schmidt & Yip 1985) and about 50 % of the adult rat lumbar sensory neurons can bind NGF with high affinity (Richardson et al 1986). BDNF and NT-3 are also retrogradely transported from an injection site in the sciatic nerve to the dorsal root ganglia (DRG) and motoneurons of adult rats (DiStefano al.…”
Section: Introductionmentioning
confidence: 99%